Blue-State Republican How Larry Hogan Won Where Republicans Lose and Lessons for a Future GOP. - Kromer, Mileah K. (Temple University Press, 2022)
"A political scientist's perspective on the rise of Republican Larry Hogan as governor of the heavily Democratic state of Maryland and what lessons the Republican Party might learn from his success"--